Implementation of Tax Compliance at PT GPW - Rico Wirayudha; Thomas Sidharta (Penerbit Jurnal Indonesia, 2025)
This research aims to evaluate the implementation of tax compliance at PT GPW, a micro, small, and medium enterprise (MSME) engaged in occupational safety and health (K3) services, which is not yet registered as a Taxable Entrepreneur (non-PKP) and manages its tax obligations independently without the assistance of a tax consultant. This study is significant in evaluating tax compliance using formal indicators in accordance with PMK No. 39/PMK.03/2018 This research employs a descriptive qualitative approach with data collection techniques including semi-structured interviews, direct observation, and document study. The analysis results show that PT GPW has fulfilled the four formal compliance indicators, namely: timely submission of tax returns (SPT), absence of tax arrears, exemption from mandatory audited financial statements by a public accountant due to turnover below IDR 50 billion, and no record of criminal tax violations. However, challenges remain in the form of limited tax literacy and internal resources, which continue to affect the daily implementation of tax administration. This research shows that formal compliance can be achieved by MSMEs without professional assistance, as long as there is legal awareness, effective use of tax reporting technology, and a willingness to comply with tax regulations. These findings can serve as evaluation material for the government in designing more adaptive tax education and guidance strategies tailored to the characteristics of MSMEs.